VD_FINDINFO Jug / 2010 / 10 vom 2. Dezember 2009 - VD Tribunal cantonal (2009)
DIVORCE, PRÉVOYANCE PROFESSIONNELLE, PRESTATION DE LIBRE PASSAGE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 al. 1 CC, 122 al. 2 CC, 123 al. 2 CC, 142 al. 2 CC, 22 al. 1 LFLP, 22 al. 2 LFLP, 15 al. 2 LPP, 7 OLP, 8a OLP, 12 OPP2